Development of ultrasonic waveguide — screw for external fixation device (Ilizarov apparatus) - D. A. Sedykh; А. А. Novikov; A. R. Putintseva; A. M. Badamshin (Омский научный вестник)
As a result of the study, an ultrasonic waveguide - screw for the Ilizarov apparatus is developed, designed and manufactured, which serves to directly affect the bone through the surgical wound with the possibility of multiple ultrasound exposure during treatment. The use of a waveguide-screw reduces the time needed to consolidate the fracture and reduce the frequency of complications associated with bone tissue regeneration and infection.